Activins and their related proteins in colon carcinogenesis: insights from early and advanced azoxymethane rat models of colon cancer. Issue 1 (December 2016) - Refaat, Bassem; El-Shemi, Adel; Mohamed, Amr; Kensara, Osama; Ahmad, Jawwad; Idris, Shakir
Abstract Background Activin-A may exert pro- or anti-tumorigenic activities depending on cellular context. However, little is known about its role, or the other mature activin proteins, in colorectal carcinoma (CRC). This study measured the expression of activin βA- & βB-subunits, activin type IIA & IIB receptors, smads 2/3/4/6/7 and follistatin in CRC induced by azoxymethane (AOM) in rats. The results were compared with controls and disseminated according to the characteristics of histopathological lesions. Methods Eighty male Wistar rats were allocated into 20 controls and the remaining were equally divided between short 'S-AOM' (15 weeks) and long 'L-AOM' (35 weeks) groups following injecting AOM for 2 weeks. Subsequent to gross and histopathological examinations and digital image analysis, the expression of all molecules was measured by immunohistochemistry and quantitative RT-PCR. Activin-A, activin-B, activin-AB and follistatin were measured by ELISA in serum and colon tissue homogenates. Results Colonic pre-neoplastic and cancerous lesions were identified in both AOM groups and their numbers and sizes were significantly (P < 0.05) greater in the L-AOM group. All the molecules were expressed in normal colonic epithelial cells. There was a significantly (P < 0.05) greater expression of βA-subunit, IIB receptor and follistatin in both pre-neoplastic and cancerous tissues. Oppositely, a significant (P < 0.05) decrease in the remaining molecules was detected in both AOM groups. Metastatic lesions were only observed within the L-AOM group and were associated with the most significant alterations of all molecules. Significantly higher concentrations of activin-A and follistatin and lower activin-AB were also detected in both groups of AOM. Tissue and serum concentrations of activin-A and follistatin correlated positively, while tissue activin-AB inversely, and significantly with the numbers and sizes of colonic lesions. Conclusions Normal rat colon epithelial cells are capable of synthesising, controlling as well as responding to activins in a paracrine/autocrine manner. Colonic activin systems are pathologically altered during tumorigenesis and appear to be time and lesion-dependent. Activins could also be potential sensitive markers and/or molecular targets for the diagnosis and/or treatment of CRC. Further studies are required to illustrate the clinical value of activins and their related proteins in colon cancer.